Bio-activation of waste mica through potassium solubilizing bacteria and rice residue - RANI, KHUSHBOO; BISWAS, DIPAK RANJAN; BHATTACHARYYA, RANJAN; BISWAS, SUNANDA; DAS, TAPAS KUMAR; BANDYOPADHYAY, KALI KINKAR; KAUSHIK, RAJEEV (The Indian Journal of Agricultural Sciences, 2022)
This article aims to demonstrate the increase in availability of potassium (K) from mica through bio-activation using different strains of potassium solubilizing bacteria (KSB) and rice residue incorporation and comparing it with standard K-fertilizer i.e. muriate of potash (MOP). The effects of mica, rice residue and KSB on wheat biomass yield, K uptake and available K in soil were assessed through a pot culture study at research farm of ICAR-Indian Agricultural Research Institute, New Delhi (2019). Results reveal that mica application @ 50 and 100 mg/kg soil significantly improved the biomass yield and K uptake by wheat as compared to treatments without mica application. Rice residue incorporation @ 2 g/kg soil had significant role in improvement of biomass yield, K uptake by wheat and available K in soil as compared to no residue treatments. Amongst the two isolated strains of KSB (JHKSB1 and JHKSB4) and one standard strain (Bacillus sp.), all were found equally effective in improving K availability from mica to the wheat crop. Mica, bio-activated via rice residue and KSB was able to improve relative agronomic efficiency and per cent K recovery from soil but it was not as effective as MOP. Thus, inherent K content in mica may be available to crops partly after bio-activation and it can be applied in conjunction with MOP for meeting the K requirement of the crop.